Temporal representation of the essences of the subject area for the construction of explanations in intelligent systems - Chalyi, Serhii; Leshchynskyi, Volodymyr (Національний технічний університет "Харківський політехнічний інститут", 2022)
The subject of research in the article is the processes of constructing explanations in intelligent systems using causal relationships. The aim is to develop a representation of the entities of the subject area, taking into account the temporal aspect in order to represent the binary relations in time between the properties of the same entity. The construction of temporal relations between the properties of entities makes it possible to determine the probabilistic causal relationships between the states of these entities and use these dependencies to form explanations for the implemented decision-making process in the intelligent system, taking into account possible alternatives. Tasks: structuring the objects of the subject area, taking into account their essential properties for the decision-making process, including temporal; definition of classes of essences of subject area; determination of equivalence classes of entities of the subject area taking into account changes in the properties of these entities over time; development of a temporal model of representation of essences of subject area for construction of explanations in intellectual systems on the basis of definition of dependences in time between properties of essences. The approaches used are: set-theoretic approach, which is used to describe the classes of entities and classes of equivalence of entities of the subject area; linear temporal logic, which provides a representation of the relationship between entities in the temporal aspect. The following results were obtained. The structuring of the objects of the subject area is performed taking into account their properties, which are used in the decision-making process in the intellectual system; defined classes of entities; the classes of equivalence of entities of the subject area are defined as a kind of class of entities with the same values of key attributes, which makes it possible to take into account changes in these values over time; a temporal model of representation of the essences of the subject area is developed, which takes into account their static, dynamic properties and properties of time. Conclusions. The scientific novelty of the results is as follows. An equivalence class for entities is distinguished, which contains entities with the same key static properties and different dynamic properties considering the time of their change, which allows to reflect changes in the state of the entity in the decision-making process in the intelligent system. The temporal model of representation of essences of subject area which contains classes of equivalence of essences, and also temporal communications between properties of elements of these classes is offered. The selection of classes of equivalence of entities makes it possible to present the decision-making process in the intellectual system in the form of a sequence of temporal connections between the properties of entities of the subject area, and to form on this basis casual relationships between states of entities.

Предметом вивчення в статті є процеси побудови пояснень в інтелектуальних системах з використанням причинно-наслідкових залежностей. Метою є розробка представлення сутностей предметної області з урахуванням темпорального аспекту з тим, щоб представити бінарні відношення у часі між властивостями однієї й тієї ж сутності. Побудова темпоральних відношень між властивостями сутностей дає можливість визначити ймовірнісні каузальні залежності між станами цих сутностей і використати ці залежності для формування пояснень щодо реалізованого процесу прийняття рішення в інтелектуальній системі з урахуванням можливих альтернатив такого процесу. Завдання: структуризація об'єктів предметної області з урахуванням їх суттєвих для процесу прийняття рішень властивостей, в тому числі темпоральних; визначення класів сутностей предметної області; визначення класів еквівалентності сутностей предметної області з урахуванням змін властивостей цих сутностей з часом; розробка темпоральної моделі представлення сутностей предметної області для побудови пояснень в інтелектуальних системах на основі визначення залежностей у часі між властивостями сутностей. Використовуваними підходами є: теоретико-множинний підхід, який застосовується для опису класів сутностей та класів еквівалентності сутностей предметної області; лінійна темпоральна логіка, яка забезпечує представлення відношень між сутностями у темпоральному аспекті. Отримані наступні результати. Виконано структуризацію об'єктів предметної області з урахуванням їх властивостей, які використовуються у процесі прийняття рішень в інтелектуальній системі; визначено класи сутностей; визначено класи еквівалентності сутностей предметної області як різновид класу сутностей з однаковими значеннями ключових атрибутів, що дає можливість врахувати зміни цих значень з часом; розроблено темпоральну модель представлення сутностей предметної області, яка враховує їх статичні, динамічні властивості та властивості часу. Висновки. Наукова новизна отриманих результатів полягає в наступному. Виділено клас еквівалентності для сутностей, який містить сутності із однаковими ключовими статичними властивостями й різними динамічними властивостями з урахуванням часу їх зміни, що дає можливість відобразити зміни стану сутності у процесі прийняття рішення в інтелектуальній системі. Запропоновано темпоральну модель представлення сутностей предметної області, яка містить класи еквівалентності сутностей, а також темпоральні зв'язки між властивостями елементів цих класів. Виділення класів еквівалентності сутностей дає можливість представити процес прийняття рішення в інтелектуальній системі у вигляді послідовності темпоральних зв'язків між властивостями сутностей предметної області, та сформувати на цій основі казуальні залежності між станами сутностей з подальшою побудовою пояснень як ланцюжка каузальних залежностей.
Темпоральне представлення сутностей предметної області для побудови пояснень в інтелектуальних системах
Keywords: intellectual system; explanation; essence; causality; causation; temporality; інтелектуальна система; пояснення; сутність; каузальність; причинно-наслідковий зв'язок; темпоральність